Integrated open Leontief model for analysis of biomass pellet demand in Thailand - Buasan, Prangvalai; Sajjakulnukit, Boonrod; Bowonthumrongchai, Thongchart; Gheewala, Shabbir H. (International Journal of Renewable Energy Development, 2025)
This study addresses the critical challenge of sustainably meeting the growing demand for biomass pellets in Thailand, particularly in light of increasing global interest in renewable energy sources. By introducing an innovative approach through the integration of the Open Leontief Model, this research constructs Input-Output Tables (IOTs) specific to the biomass pellet sector, encompassing 180 economic sectors. The study evaluates the economic impacts of varying domestic and international demand scenarios on Thailand’s economy. Utilizing mass and energy balance methodologies, it provides a comprehensive analysis of the biomass pellet supply chain, from plantation to pelletization, for both corn and wood pellets. Findings reveal significant economic intersectoral linkages within Thailand's economy, indicating the biomass pellet sector's potential to substantially contribute to national renewable energy targets and reduce fossil fuel dependency. Notably, the sector is projected to require an increase in raw materials, energy, and other inputs by 3.8% in 2024 and 2.63% in 2036, following the trend of international biomass pellet demand. Additionally, employment in the sector is expected to increase by 3.8% annually under international demand scenarios and 4.6% annually under domestic and international demand scenarios. The research concludes with policy recommendations aimed at fostering sector growth, emphasizing the importance of government incentives, capacity building, and the establishment of biomass plantation communities to meet the increasing demand for biomass pellets. This study not only sheds light on the sector's current state but also charts a path forward for sustainable energy solutions in Thailand in line with Sustainable Development Goals 7, 8, and 9. Together, these initiatives aim to ensure a balanced transition toward renewable energy, benefiting both the economy and the environment.